2009
DOI: 10.1177/0739986308327502
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, Stress, and Acculturation Among Dominican Immigrant Women

Abstract: Researchers have well established the association between discriminatory experiences, life chances, and mental health outcomes among Latino/as, especially among Mexican Americans. However, few studies have focused on the impact of stress or the moderating effects of low acculturation levels among recent immigrants, such as Dominicans. Using the transactional stress model, the present community-based study examines the relationship between discrimination and stress, and whether this association varies by low ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 44 publications
2
32
0
8
Order By: Relevance
“…Concomitantly, the Latino community experiences higher levels of perceived and actual discrimination (Hovey, Rojas, Kain, & Magaña, 2000). There is substantial evidence supporting the negative effects of discrimination on individuals mental health (Araújo Dawson, 2009; Gee, Ryan, Laflamme, & Holt, 2006; Moradi & Risco, 2006; Umaña-Taylor & Updegraff, 2007; Yip, Gee, & Takeuchi, 2008). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Concomitantly, the Latino community experiences higher levels of perceived and actual discrimination (Hovey, Rojas, Kain, & Magaña, 2000). There is substantial evidence supporting the negative effects of discrimination on individuals mental health (Araújo Dawson, 2009; Gee, Ryan, Laflamme, & Holt, 2006; Moradi & Risco, 2006; Umaña-Taylor & Updegraff, 2007; Yip, Gee, & Takeuchi, 2008). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Maintaining a Latino orientation can provide a protective function by providing individuals access to traditional cultural resources. A recent study provided support for this notion and reported that retention of the traditional Latino culture moderated the relationship between everyday discrimination and general stress among a sample of Dominican women (Araujo Dawson, 2009). However, contrary evidence has shown that a Latino orientation augmented the relationship between perceived discrimination and anxiety among Latino college students (Alamilla et al, 2010).…”
mentioning
confidence: 92%
“…Among Mexican-origin youth, perceived discrimination emerges within a larger cultural context; a context characterized by the process of dual-cultural adaptation—adaptation to the majority culture ( acculturation ) and adaptation to (or retention of) their culture of origin ( enculturation ; Gonzales, Fabrett & Knight, 2009). Evidence suggests that cultural orientations may play a role in the ways that Latinos experience stress (Araújo Dawson, 2009; Umaña-Taylor & Updegraff, 2007). However, research rarely considers the duality of cultural orientations (e.g., how mainstream orientations interact with ethnic-specific orientations) in the stress process.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this literature have revealed, for instance, that among Dominican immigrant women, enculturative behavioral orientations (i.e., Spanish media and music use) interacted with everyday discrimination to predict feelings of stress (Araújo Dawson, 2009); here, enculturative orientations proved protective, mitigating the link between discrimination and feelings of stress. In another study of primarily Mexican-origin adults, Anglo orientations moderated the association between perceived discrimination and acculturative stress, with Anglo orientations operating as a protective factor to minimize the relation between discrimination and feelings of stress (Torres, Driscoll & Voell, 2012).…”
Section: Introductionmentioning
confidence: 99%